Can CT measures of tumour heterogeneity stratify risk for nodal metastasis in patients with non-small cell lung cancer?. Issue 10 (October 2017) - Craigie, M.; Squires, J.; Miles, K.
Abstract : Aim: To undertake a preliminary assessment of the potential for computed tomography (CT) measurement of tumour heterogeneity to stratify risk of nodal metastasis in patients with non-small cell lung cancer (NSCLC). Materials and methods: Tumour heterogeneity in CT images from combined positron-emission tomography (PET)/CT examinations in 150 consecutive patients with NSCLC was assessed using CT texture analysis (CTTA). The short axis diameter of the largest mediastinal node was also measured. Forty-two patients without distant metastases subsequently had tumour nodal status confirmed at surgery ( n= 26) or endobronchial ultrasound (EBUS; n= 16). CTTA parameters and largest nodal diameter were related to nodal status using the rank correlation and the risk ratio for each nodal stage (>N0, >N1, >N2) was compared between patients categorised as high and low risk by CTTA or nodal size. The most significant predictor of nodal status was related to overall survival using Kaplan–Meier analysis. Results: N-stage was more significantly correlated with CTTA than nodal diameter (Rs = -0.39, p= 0.011, Rs = -0.45, p= 0.0025, Rs = -0.40, p= 0.0091 for normalised standard deviation (SD), normalised entropy and kurtosis respectively; Rs = -0.39, p= 0.042 for nodal diameter). The presence of two or more high-risk CTTA values was the greatest risk factor for mediastinal metastasis (risk ratio: 11.0, 95% confidence interval: 1.56–77.8, p= 0.0014) and was associated with significantly poorer overall survival ( p= 0.016). Conclusion: CTTA in NSCLC is related to nodal status in patients without distant metastases and has the potential to inform selection of investigative strategies for the assessment of mediastinal malignancy. Highlights: CT texture analysis (CTTA) is emerging as a technique for derivation of prognostic biomarkers for patients with NSCLC. CT texture analysis evaluates quantitatively tumour heterogeneity, which is linked to tumour aggression. CTTA in NSCLC is related to nodal status in patients without distal metastases and has potential to inform selection of investigative strategies for the assessment of mediastinal malignancy.